Structural, electronic and mechanical properties of a novel graphenylene-like structure based on GeC - Martins, Nicolas F. [UNESP]; Laranjeira, José A.S. [UNESP]; Azevedo, Sérgio A. [UNESP]; Fabris, Guilherme S.L.; Sambrano, Julio R. [UNESP] (Elsevier, 2023)
In recent years, several atomically thin two-dimensional (2D) materials have been reported with remarkable properties that prospect them as potential structures for nanotechnological applications. Advancing the research of layered structures, in this work, a new 2D inorganic material based on germanium carbide (GeC) and characterized by 4-, 6- and 12-membered rings, named inorganic graphenylene-like germanium carbide (IGP-GeC), is proposed via density functional theory (DFT) simulations to predict its structural, electronic, and mechanical properties. This structure has a direct band gap energy (2.65 eV), which can be modulated from 3.39 eV to a conductor character by applying a biaxial strain (ε) from −12% to 12%, making it a promising contender for nanoelectronics applications. IGP-GeC has an in-plane dielectric constant of 7.15 that increases with tensile strain, reaching 10.51 (ε = 12%), an exciting result in comparison with other 2D materials, also leading to remarkable excitonic properties in both unstrained and strained conditions. Besides this, the effective masses analysis denotes great stability of the charge carriers for IGP-GeC, improved by the tensile strain application. Finally, molecular dynamics (MD) simulations show that IGP-GeC is stable at 1200 K, and the absence of imaginary modes in the phonon bands attests to the dynamical stability of this novel 2D material, which will be useful to experimentalists in further studies.
Keywords: 2D materials; Biphenylene; DFT; GeC; Graphenylene